2013
DOI: 10.1136/annrheumdis-2012-202786
|View full text |Cite
|
Sign up to set email alerts
|

Tendon involvement in the feet of patients with gout: a dual-energy CT study

Abstract: Tendons are commonly affected by MSU crystal deposition in patients with tophaceous gout. The patterns of MSU crystal deposition suggest that biomechanical strain or other local factors may contribute to deposition of MSU crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 16 publications
10
73
0
Order By: Relevance
“…Contrary to our hypothesis, our results indicate that the dorsiflexors of the ankle are not affected by strength deficits to the same extent as the plantarflexors of the ankle in people with gout. This finding may be related to the pattern of crystal deposition and patient symptoms reported in the foot and ankle, in which anterior ankle structures, including the tibialis anterior tendon are less frequently involved compared with the posterior ankle and Achilles tendon [6,8]. Our results are consistent with previous studies investigating the ankle in other chronic inflammatory arthritic conditions [27] in which neural…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Contrary to our hypothesis, our results indicate that the dorsiflexors of the ankle are not affected by strength deficits to the same extent as the plantarflexors of the ankle in people with gout. This finding may be related to the pattern of crystal deposition and patient symptoms reported in the foot and ankle, in which anterior ankle structures, including the tibialis anterior tendon are less frequently involved compared with the posterior ankle and Achilles tendon [6,8]. Our results are consistent with previous studies investigating the ankle in other chronic inflammatory arthritic conditions [27] in which neural…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has observed tophaceous deposition in the Achilles, peroneal and the tibialis posterior muscle tendons in people with gout [6,8]. Tendons have important functional roles, both in generating and absorbing mechanical work during ambulation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gout is a chronic disease of monosodium urate (MSU) crystal deposition, with a predilection for peripheral sites in the lower limbs [1,2]. The presence of MSU crystals initiate local inflammation resulting in self-limiting flares of acute gouty arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, unless urate lowering therapy (ULT) is started and continued long-term to reduce the serum urate below saturation concentrations, patients can develop progressive disease, with recurrent A qualitative study to explore health professionals' experience of treating gout: understanding perceived barriers to effective gout management ORIGINAL SCIENTIFIC PAPER ORIGINAL RESEARCH attacks, gouty tophi, joint damage, and limitation of quality of life. 6,7 There are low national rates of continuous allopurinol prescription and serum urate monitoring in NZ. 8 To date no qualitative data exist on the perspective of NZ health professionals as to why gout treatment remains suboptimal.…”
Section: Introductionmentioning
confidence: 99%